2007
DOI: 10.1105/tpc.107.052274
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis TRANSPARENT TESTA GLABRA2Is Directly Regulated by R2R3 MYB Transcription Factors and Is Involved in Regulation ofGLABRA2Transcription in Epidermal Differentiation

Abstract: Arabidopsis thaliana TRANSPARENT TESTA GLABRA2 (TTG2) encodes a WRKY transcription factor and is expressed in young leaves, trichomes, seed coats, and root hairless cells. An examination of several trichome and root hair mutants indicates that MYB and bHLH genes regulate TTG2 expression. Two MYB binding sites in the TTG2 59 regulatory region act as cis regulatory elements and as direct targets of R2R3 MYB transcription factors such as WEREWOLF, GLABRA1, and TRANSPARENT TESTA2. Mutations in TTG2 cause phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
176
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(185 citation statements)
references
References 43 publications
6
176
0
3
Order By: Relevance
“…In addition, we showed that tissue-specific mutant transcriptome information can be used to help define the function of an uncharacterized gene in the root epidermal network (the TTG2 gene). Indeed, our data uncovered a role for TTG2 in hair cell specification, an unexpected finding given that TTG2's gene expression and protein accumulation is preferentially observed in non-hair cells (Ishida et al, 2007).…”
Section: Using Molecular Phenotypes To Define Gene Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, we showed that tissue-specific mutant transcriptome information can be used to help define the function of an uncharacterized gene in the root epidermal network (the TTG2 gene). Indeed, our data uncovered a role for TTG2 in hair cell specification, an unexpected finding given that TTG2's gene expression and protein accumulation is preferentially observed in non-hair cells (Ishida et al, 2007).…”
Section: Using Molecular Phenotypes To Define Gene Functionmentioning
confidence: 98%
“…To test this, we analyzed the root epidermis transcriptome of a mutant affecting TRANSPARENT TESTA GLABRA2 (TTG2), which encodes a WRKY-type transcription factor required for anthocyanin and trichome production (Johnson et al, 2002). TTG2 is presumed to have a role in nonhair epidermis development, due to its preferential expression in differentiating non-hair cells (Johnson et al, 2002;Bruex et al, 2012) (see Supplemental Figure 2A online) and the dependence of this expression on WER, GL3/EGL3, TTG, and CPC/TRY (Ishida et al, 2007;Bruex et al, 2012) (see Supplemental Figure 2B online). However, TTG2's role in the root epidermis is unclear, principally because ttg2 mutants lack a morphological phenotype (Johnson et al, 2002) (Figures 4A and 4B).…”
Section: Defining the Role Of Ttg2 Through Mutant Transcript Profilingmentioning
confidence: 99%
“…Transgenic plants expressing a chimeric repressor version of the TTG2 protein (TTG2: SRDX) showed defects in trichome formation, anthocyanin accumulation, seed color pigmentation and differentiation of root hairless cells. GLABRA2 (GL2) expression was markedly reduced in roots of ProTTG2:TTG2:SRDX transgenic plants, suggesting that TTG2 is involved in the regulation of GL2 expression, although GL2 expression in the ttg2 mutant was similar to that in the wild type and this suggests a new step in a regulatory cascade of epidermal differentiation (Ishida et al 2007). …”
Section: Trichome Developmentmentioning
confidence: 99%
“…In Arabidopsis, a ternary complex composed of R2R3-Myb transcription factors [GLABRA1 (GL1; previously known as GLABROUS1) (Oppenheimer et al, 1991) or MYB23 (Kirik et al, 2005)], bHLH transcription factors [GLABRA3 (GL3) (Payne et al, 2000) or ENHANCER OF GLABRA3 (EGL3) (Zhang et al, 2003)] and the WD40 repeat protein TRANSPARENT TESTA GLABRA1 (TTG1) acts at the top of the regulatory hierarchy of trichome development. The Myb-bHLH-WD40 complex activates the expression of multiple downstream factors, each of which directs the morphogenesis or lateral inhibition of the developing trichomes (Szymanski et al, 1998;Schellmann et al, 2002;Ishida et al, 2007;Zhao et al, 2008). Thus, the current model of trichome patterning comprises a local autonomous circuit of multiple transcription factors acting at leaf primordia (Pesch and Hülskamp, 2004;Bouyer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%